Impact of four times daily dosing of oral treprostinil on tolerability and daily dose achieved in pulmonary hypertension. (1st November 2017) - Coons, James C.; Bunner, Cheryl; Ishizawar, David C.; Risbano, Michael G.; Rivera‐Lebron, Belinda; Mathier, Michael A.; Chan, Stephen Y.; Simon, Marc A.
Abstract : Oral treprostinil (TRE) is a prostacylin that is approved for the treatment of patients with pulmonary arterial hypertension (PAH). Dosing is approved for two or three times daily (t.i.d.); however, adverse effects, including gastrointestinal‐related symptoms, may limit the ability to reach optimal doses. We report our experience with a four times daily (q.i.d.) regimen of oral TRE for goal‐directed therapy of PAH. We describe three patients that were transitioned from infusion or inhaled TRE to oral TRE with initial t.i.d. dosing over a four‐day hospital stay. All patients were subsequently further dose‐adjusted in the outpatient setting; however, adverse effects limited additional up‐titration despite persistent dyspnea. In a carefully monitored outpatient setting, patients were switched from t.i.d. to q.i.d. dosing of oral TRE. All three patients were successfully dosed q.i.d., having achieved a higher total daily dose compared with a t.i.d. dose regimen. Furthermore, patients were able to maintain functional class II symptoms with mitigation of adverse effects using the q.i.d. dose regimen.